Pengaruh School Climate, Keadilan Organisasi, dan Komitmen Organisasi terhadap Organizational Citizenship Behavior di Sekolah XYZ Jakarta - Yenny Widjaja (Jurnal Ketopong Pendidikan, 2024)
This study aims to determine the effect of school climate, organizational justice, organizational commitment on organizational citizenship behavior at Sekolah XYZ, Pluit Village. In this study, the population was 41 respondents. Data obtained from closed questionnaires that have been tested for validity and reliability. The collected data was analyzed by descriptive analysis, while hypothesis testing using path analysis and technical data analysis using smartPLS software. The results showed that (1) the organizational commitment has a positive effect on organizational citizenship behavior, (2) organizational justice has a positive effect on organizational commitment, (3) organizational justice has a positive effect on organizational citizenship behavior, (4) the school climate has a positive effect on organizational commitment, and (5) the school climate has a positive effect on organizational citizenship behavior. The implication of this research is that school creates and maintains a positive school climate, organizational justice, organizational commitment that will have a good impact on organizational citizenship behavior. A number of suggestions on managerial theory and implementation were proposed too.